Construction waste management: Level of practice of contractors / Wan Zukri Wan Abdullah and Ahmad Ruslan Mohd Ridzuan - Wan Abdullah, Wan Zukri; Mohd Ridzuan, Ahmad Ruslan (Universiti Teknologi MARA Cawangan Pahang, 2008)
Construction wastes have become a major environmental problem not only in Malaysia but also throughout the world. Tonnes of demolition and construction wastes are produced daily. While most wastes are destined to landfill areas, some of them are disposed of and dumped illegally in private lands. Hence, if the production of wastes is not controlled and managed properly, Malaysia will eventually face major environmental problems as a result of rapid dwindling of available dumping and landfill areas. Controlling and managing construction wastes are becoming more and more eminent and important to healthier living environment of the future generation. Construction sites wastes should be managed and minimised to mitigate negative effects to the environment. This paper will look on the basic procedure of construction waste management that has been practised by the contractors. Finally, this paper will proposed basic waste management guidelines as a basic preparation that consist of three (3) main factors; basic preparation of Waste Management Plan (WMP), estimating of construction waste, and sorting or separation techniques of building waste